Intra-abdominal pressure during swimming - Moriyama, S.; Ogita, F.; Huang, Z.; Kurobe, K.; Nagira, A.; Tanaka, T.; Takahashi, H.; Hirano, Y. (International Journal of Sports Medicine, 2014)
The present study aimed to determine the intra-abdominal pressure during front crawl swimming at different velocities in competitive swimmers and to clarify the relationships between stroke indices and changes in intra-abdominal pressure. The subjects were 7 highly trained competitive collegiate male swimmers. Intra-abdominal pressure was measured during front crawl swimming at 1.0, 1.2 and 1.4 m · s-1 and during the Valsalva maneuver. Intra-abdominal pressure was taken as the difference between minimum and maximum values, and the mean of 6 stable front crawl stroke cycles was used. Stroke rate and stroke length were also measured as stroke indices. There were significant differences in stroke rate among all velocities (P<0.05). However, there was no significant difference in stroke length by velocity. Significant within-subject correlations between intra-abdominal pressure and stroke rate or stroke length (P<0.01) were observed, although there were no significant correlations between intra-abdominal pressure and stroke indices when controlling for swimming velocity. These findings do not appear to support the effectiveness of trunk training performed by competitive swimmers aimed at increasing intra-abdominal pressure.